Leveraging Technology As a Response to the COVID Pandemic : Adapting Diverse Technologies, Workflow, and Processes to Optimize Integrated Clinical Management - Frisch, Paul H.; Pappas, Harry P. (New York, NY ; Abingdon, Oxon : Routledge, 2023)
This timely and important book describes the impact on the hospital ability to provide patient care and how healthcare institution leveraged diverse technology solutions to combat impact of COVID-19 on providing patient care.
OCLC-licensed vendor bibliographic record.
Keywords: Hospital care -- Technological innovations; COVID-19 (Disease) -- Treatment; COVID-19 Pandemic, 2020- -- Influence; MEDICAL / Health Risk Assessment; MEDICAL / Infectious Diseases